Structure of twisted and buckled bilayer graphene. (15th November 2016) - Jain, Sandeep K; Juričić, Vladimir; Barkema, Gerard T
Abstract: We study the atomic structure of twisted bilayer graphene, with very small mismatch angles ( θ ∼ 0.28 0 ), a topic of intense recent interest. We use simulations, in which we combine a recently presented semi-empirical potential for single-layer graphene, with a new term for out-of-plane deformations, (Jain et al   2015 J. Phys. Chem. C119 9646 ) and an often-used interlayer potential (Kolmogorov et al 2005 Phys. Rev. B71 235415 ). This combination of potentials is computationally cheap but accurate and precise at the same time, allowing us to study very large samples, which is necessary to reach very small mismatch angles in periodic samples. By performing large scale atomistic simulations, we show that the vortices appearing in the Moiré pattern in the twisted bilayer graphene samples converge to a constant size in the thermodynamic limit. Furthermore, the well known sinusoidal behavior of energy no longer persists once the misorientation angle becomes very small ( θ < 1 0 ). We also show that there is a significant buckling after the relaxation in the samples, with the buckling height proportional to the system size. These structural properties have direct consequences on the electronic and optical properties of bilayer graphene.